Performance of Broiler Chickens Reared in Postal, Stage, and Closed House Cage - Henni Vanda Henni Vanda; Titania Titania; Wahyu Eka Sari; Muhammad Hambal; Fadli A. Gani (Universitas Syiah Kuala, 2023)
Broiler chickens have high productivity in producing meat. This study aimed to determine the increase of chickens’ body weight and to determine the performance index and the mortality rate between postal, stage, and closed house cages. This study used 72 broiler chickens, the experiment was carried out on the chickens aged 10 days and 25 days old. This research was conducted at the University Teaching Farm, Universitas Syiah Kuala, which is located in Ie Seum village, Aceh Besar district. The results showed that at the age of 10 days, the average body weight was 340 g in postal cage, 365 g in stage cage, and 415 g in closed house cage. The average body weight of 25 days old chicken was 1554 g in postal cage, 1605 g in stage cage, and 1718 g in closed house. Based on analysis of variance (ANOVA) body weight of broiler chickens aged 10 days showed significant difference in every cage (P0,05) and broiler chickens at the age of 25 days showed a significant difference (P0,05) in closed house. In this study, closed house cage obtained the highest body weight. Mortality rate of broiler chickens in closed house was 1.84%, postal cages was 3.60% and stage cage was 3.47%. The Performance Index (PI) of broiler chickens was 449 in closed house, 387 in postal cage and 376 in the stage cage. The highest PI was found in closed house cage and categorized as outstanding. It can be concluded that closed house cage had the highest body weight, the best performance index and the lowest mortality rate.